Aspek Imunitas pada COVID-19 - Nitiyoso, Nugroho (Cermin Dunia Kedokteran, 2021)
Gejala COVID-19 sangat bervariasi dari ringan hingga berat. Selain faktor komorbiditas, reaksi imun yang berbeda-beda antar pasien juga menjadi faktor yang memengaruhi berat-ringannya gejala COVID-19. Kenaikan kadar sitokin diduga menjadi faktor yang memperberat gejala COVID-19. Dalam artikel ini, akan dibahas aspek respons imun serta sitokin yang memengaruhi gejala COVID-19, serta beberapa pengobatan imunologi yang sedang diteliti untuk COVID-19.Symptoms in COVID-19 patients vary widely from mild to severe. In addition to comorbidities, different immune reactions among patients are also a factor that affects the severity of COVID-19 symptoms. The increase in cytokine levels is thought to be a factor that aggravates the symptoms of COVID-19. In this article, we will discuss aspects of the immune response and cytokines that affect the symptoms of COVID-19, as well as some of the immunological treatments currently being studied for COVID-19.